NOBLE MORAL DEVELOPMENT THROUGH THE TEACHER'S EXAMPLE AT MADRASAH ALIYAH MUHAMMADIYAH 1 MEDAN - Dianto, Dian (Proceeding International Seminar of Islamic Studies, 2023)
Coaching through the example of teachers is needed in the world of education. With the development of noble character will make these students become faithful, moral and have knowledge. This research is a qualitative research by taking several activities starting from observation, interviews, and documentation. The results of this study show that firstly, the development of noble character in Madrasah Aliyah Muhammadiyah 1 Medan becomes routine and incidental. Second, the development of morals regarding discipline and religion is ongoing. Third, the evaluation is carried out in the form of a monthly meeting which contains a report on the extent of the guidance they have carried out with the madrasah head as controlling. Fourth, the supporting factors are good cooperation between the Madrasah head, teachers, homeroom teachers and all education staff. While the inhibiting factor is the interaction of students outside class hours with the outside environment which sometimes leads to a negative direction.  The exemplary forms shown by teachers include time discipline, discipline in enforcing rules, discipline in behavior, discipline in worship. The conclusion in this study is that students at Madrasah Aliyah Muhammadiyah 1 Medan already have noble character that can be applied in everyday life, so that in the future they can continue to higher education and achieve their goals.